Analisis Penerapan Pelayanan Antrian Dapodik Berbasis Online dan Interaksi Tatap Muka - Duwi Febyanti; Sri Rahayu (CV. Shofanah Media Berkah, 2025)
The Data Pokok Pendidikan (Dapodik) service plays a crucial role in educational administration, requiring accurate data, fast processing, and easy access for school operators. In practice, the Provincial Education Office of South Sumatra provides two types of services: online services and face-to-face services. Each mechanism has its own strengths and weaknesses. Face-to-face services often result in long queues, unmeasured waiting times, and crowding during peak periods. Meanwhile, the online service through the s.id/antriandapodik platform offers more accessible processing but still lacks key features such as estimated waiting time, real-time queue status, and automated notifications. This practical work research aims to analyze the effectiveness of both service mechanisms and to develop a more structured online queueing system. The study uses a Research and Development (R&D) approach with the Waterfall model, including needs analysis, system design, development, and evaluation. Data were collected through observation, interviews, documentation, and questionnaires. The results show that implementing an online queueing system equipped with digital queue numbers, scheduled visits, a monitoring dashboard, and automated notifications successfully reduces physical queues by up to 40%, increases time efficiency, and helps staff better manage daily workloads. Furthermore, user satisfaction significantly improves, especially in terms of accessibility and transparency of service processes. The study concludes that online and face-to-face services complement each other. Online services are more effective for simple administrative tasks, while face-to-face services remain essential for complex cases that require direct verification. Integrating both service models is recommended to create a more efficient, modern, and responsive Dapodik service system.